ASSET INSTRUMEN KEUANGAN DAN FREE CASH FLOW TERHADAP NILAI PERUSAHAAN: DIVIDEND PAYOUT RATIO SEBAGAI PEMODERASI - SUWALDIMAN SUWALDIMAN; JAMHARI RAMADHAN (Jurnal Bisnis dan Akuntansi, 2019)
This research examines the impact of financial instrument assets and free cash flow on the firm value. This research also tests the dividend payout ratio as the moderating variables. Data sample were taken out of the manufacturing companies listed in BEI for period of 2014 – 2016. Firm value is defined and measured as the share market price five days as the audit report released. Financial instrument assets is defined and measured by the ratio of the total financial assets to the total assets. Meanwhile free cash flow is measured by comparing the operating cash flows less by capital expenditure to the operating cash flow. Finally, dividend payout is measured by the ratio of dividend per share to the earnings per share. Regression analysis is employed to test relationship among those variables. This research reveals that the financial instrument assets have a positive and significant impact on the firm value. However, this research does not prove that the free cash flow has a positive and significant impact on the firm value. Moreover, the dividend payout ratio strengthens the impact of financial instrument assets on the firm value, but not the free cash flow. It can be concluded that market will respond positively to the information of increasing in the financial instrument assets. And the increasing in the dividend payout ratio will strengthen to the relationship. In contrast, free cash flow is not significantly responded by the market and either the dividend payout ratio.